Design and Analysis of IoT Systems for Fuel Consumption Monitoring on Offshore Vessels with Economic Analysis Approach - Sahdha Prakasa; Erma Suryani (Journal of Social Research, 2025)
Fuel consumption represents one of the largest cost components in ship operations, making real-time fuel consumption monitoring a crucial need for shipping companies. PT Pelayaran Nasional Ekalya Purnamasari faces challenges in managing fuel efficiency due to limitations of manual monitoring systems that cannot detect anomalies quickly and accurately. This study aims to design and implement an Internet of Things (IoT)-based fuel monitoring system using KCT-1904 devices as a digital solution to improve ship operational efficiency. The research uses a systems engineering approach through hardware assembly, software configuration, data collection, anomaly analysis, and visualization reporting stages. Sensors and cables were carefully assembled to ensure optimal integration with ship systems. Software parameters and user interfaces were configured to facilitate direct monitoring by ship operators. Fuel consumption data were collected during sailing periods, analyzed to identify usage patterns, and used to detect anomalies such as abnormal fuel consumption spikes. The results show that the KCT-1904 monitoring system can provide accurate reports, detect anomalies in real-time, and identify technical issues that can be addressed promptly. With the implementation of this system, PT Pelayaran Nasional Ekalya Purnamasari has the potential to increase fuel efficiency, improve operational performance, and reduce costs related to ship fuel consumption. This study also produces a conceptual design of a fuel monitoring information system that can be further developed to support digital transformation in the national shipping industry.